(untitled) (TAMADDUN NURI JURNALI, 2024)
The current research paper deals with the nature of word order in conversational language. It focuses readers’ attention the language phenomenon as ellipsis, cleft and substitution and their impact on the types and degrees of the expression of the thought, feeling and ideas in conversation process. The main issue of the article is importance of word order in the expression of speaker’s attitude towards the dictum in different types of speech acts